Assessment of Adherence to Prescribed Therapy in Patients with Chronic Hepatitis B. Issue 1 (March 2016) - Abreu, Rodrigo; Silva Ferreira, Camila; Ferreira, Aline; Remor, Eduardo; Nasser, Paulo; Carrilho, Flair; Ono, Suzane
Abstract Introduction Evidence shows that treatment for hepatitis B virus (HBV) can suppress viral load. Among the factors directly linked to therapeutic success is adherence to the treatment. Several instruments to assess adherence are available, but they are not validated for use in chronic hepatitis B. The purpose of this paper was to adapt and validate the "Assessment of Adherence to Antiretroviral Therapy Questionnaire—HIV" (CEAT-VIH) for patients with chronic hepatitis B (referred to herein as CEAT-HBV). Methods The validity of the adapted questionnaire evidence was established through concurrent, criterion, and construct validities. Results We found negative and significant correlation between the domain "degree of compliance to antiviral therapy" assessed by CEAT-HBV and the Morisky test (r = −0.62, P < 0.001) and between the domain "barriers to adherence" and HBV viral load (r = −0.42, P < 0.001). In terms of the construct's discriminative capacity, scores greater than or equal to 80 detected antiviral therapy success, which are necessary for the prediction of an undetectable HBV viral load. Thus, a cutoff value of 80.5 was set with a value of 81% for sensitivity and 67% for specificity. Conclusion The CEAT-HBV identified 43% (n = 79) non-adherent patients and was shown to be a useful tool in clinical practice.